The change of cellular membranes on apoptosis: fluorescence detection - Demchenko, A.P. (Experimental Oncology, 2012)
The strong plasma membrane asymmetry existing in living cells is lost on apoptosis, and it is commonly detected with the probes interacting strongly and specifically with phosphatidylserine (PS). This phospholipid becomes exposed to the cell surface, and the labeled annexin V is used for its detection. The requirement for early and Ca2+-independent detection of apoptosis in the formats of spectroscopy of cell suspensions, flow cytometry, microarray technology and confocal or two-photon microscopy stimulated efforts for the development of new methods. Since the PS exposure must produce integrated changes of electrostatic potential and hydration in the outer leaflet of cell membrane, its detection can be provided by direct response of smart fluorescence probes. This review is focused on basic mechanisms underlying the loss of membrane asymmetry during apoptosis and the principles lying in the background of new methods that demonstrate essential advantages over the annexin V-binding assay. The convenient wavelength-ratiometric technique based on fluorescent probe F2N12S is described in detail. It incorporates spontaneously into outer leaflet of cell membrane and the color change of its fluorescent emission associated with apoptosis can be easily detected. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.